The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3122/jabfm.2011.03.100180
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Asthma

Abstract: Background:The purpose of this review is to describe the current understanding of the prevalence and adverse effects of cigarette smoking and secondhand smoke (SHS) in asthmatics in terms of patient outcomes and response to inhaled corticosteroids.Methods: We searched the English biomedical literature via PubMed, Embase, and Scopus using the terms "smoking and asthma," "secondhand smoke and asthma," "environmental tobacco smoke and asthma," and "smoking/secondhand smoke and corticosteroids." We also reviewed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
99
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 110 publications
(61 reference statements)
5
99
0
8
Order By: Relevance
“…These disorders lead to periodic symptoms such as wheeze or cough, especially at night. Asthma is one of the most common respiratory disorders; it affects 22 million Americans (1). Many studies reported that the prevalence of asthma is increasing (2−5).…”
Section: Introductionmentioning
confidence: 99%
“…These disorders lead to periodic symptoms such as wheeze or cough, especially at night. Asthma is one of the most common respiratory disorders; it affects 22 million Americans (1). Many studies reported that the prevalence of asthma is increasing (2−5).…”
Section: Introductionmentioning
confidence: 99%
“…Were you aware that steroid resistance occurs more often in asthma patients who smoke compared with asthma patients who do not smoke? 4 The data for this are reasonably clear and suggest that smoking asthmatic patients will respond to higher doses of steroids, when indicated. Overall, as family physicians we need to help our patients stop smoking, be aware of and work to eliminate secondhand smoke, and be aware that higher doses of steroids may be needed to gain effect in patients with asthma.…”
Section: Asthma Smoking and Steroid Dosingmentioning
confidence: 73%
“…Among these factors is exposure to passive smoking (Quinto et al, 2013), which has a deleterious effect on the prognosis of childhood asthma and induces resistance to treatment by corticosteroids (Stapleton et al, 2011;Radic et al, 2011). Recent studies still show parental smoking as the number one environmental exposure that causes asthma in the pediatric population (Nhlbi, 2007;Burke et al 2012).…”
Section: Introductionmentioning
confidence: 99%